Effect of Students Self-Directed Learning to Self-Care in Organs of Human Body Lesson on Daily Life - Reni Marlina; Dian Miranda; Marmawi Marmawi; Andri Maulidi (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
This study aims to describe the effects of self-directed learning skills on self-care for organs of the body among five-year-old children in the kindergartens of Kubu Raya District, West Kalimantan. The methods used in this study were qualitative and quantitative research methods. The results of this study showed that the respondents were able to diagnose learning needs with good criteria, had not been able to formulate learning objectives independently, were able to identify learning resources with good criteria, were able to choose and apply appropriate learning strategies, and were happy to evaluate their learning outcomes with the very good criteria. In the aspect of self-care for organs, the students had knowledge about the organs and understood how to maintain with good criteria. The students had used their time to care for organs, had not been able to describe the functions of organs, and were able to analyze knowledge about personal health with very good criteria. The results of the analysis indicates that self-directed learning affected self-care for organs of the body. It is recommended for teachers and parents to teach the human body recognition not only having an accessory but more emphasis on practice in daily life